Identity of the Literary Text - Miller, Owen J.; Valdes, Mario J. (Book collections on Project MUSE., 1985)
This book brings together, in the spirit of dialogue, the arguments on both sides of the most important issue in literary criticism today. It will be of interest to all concerned with textual theory, regardless of which literature are considered.